PATOGENICIDAD Y VIRULENCIA DE CEPAS DE BACILLUS THURINGIENSIS NATIVAS DEL ESTADO DE MORELOS SOBRE DIATRAEA MAGNIFACTELLA (LEPIDOPTERA: CRAMBIDAE) - Fonseca G., Alicia; Peña Ch., Guadalupe; Trejo L., Adriana G.; Lina G., Laura P.; Rodríguez B., Luis Á.; Hernández V., Víctor M. (Instituto de Ecología, A.C., 2013)
Sugarcane is one of the most important industrial crops in Mexico, several insects feed on it, causing important economic losses. At the state of Morelos two species are found; Diatraea magnifactella and Eoreuma loftini. To control these borers chemical insecticides are used, today there are not any bioinsecticide based on entomopathogenic bacteria. It has already been reported in the literature against other borer species the use of entomopathogenic bacteria, so in this work was proposed to isolate Bacillus thuringiensis (Bt) from cadavers of D. magnifactella to evaluate the pathogenicity and virulence of bacterial isolates on neonate larva. It was possible the establishment a colony of D. magnifactella at laboratory, ensuring the health of the larvae used in bioassays. We obtained a total of 118 bacterial isolates, presumably from B. thuringiensis. Which were grouped into three groups, depending on thier protein profile. Six of the 118 strains caused more than 50% of mortality in neonate larvae of D. magnifactella. The LC50 of isolates been defined, the best was the B148 by 254.01 ng/cm2 of food. The LC50 the commercial strain HD1 was 417.61 ng/cm2, used as appositive control. The five remaining isolates showed LC50 greater than that of the positive control.